The Dimensions of the Quality Perceived by Users in a Clinical Analysis Laboratory of A University Hospital (International Journal of Business, Economics and Management, 2020)
The perception of the user has been regarded as a sensitive indicator of the quality of health service. In addition, incorporating the vision of the user in the planning of the service is acting within the guidelines of humanization and popular participation recommended by the Single System of Health - SUS. These considerations motivated to carry out an investigation of the perception of quality of Service of Laboratory Medicine of Clinical Hospital of the Federal University of Minas Gerais - HC-UFMG - by its users. It was sought to identify the dimensions of quality associated with the Laboratory, from the perspective of the SUS’s user. 22 in-depth interviews were performed with users and two with managers. The data obtained were subjected to content analysis five dimensions of quality in the lab were found: the humanized care, efficiency in care, confidence in the quality of the laboratory, the comfort of the collection place and the cost. There was a consistency in the testimonies which allows considering that the service of Laboratory Medicine of HC-UFMG is well evaluated regarding size acceptance and trust, but it does not do a very good job when taken into account the efficiency of care - considered time consuming - and the comfort of the collection place. Also, as a result of the research, there are the subsidies for the development of a data collection instrument for assessing the quality perceived by the users of the Clinical Analysis Laboratories.